The Gospel of Freedom : Black Evangelicals and the Underground Railroad - Turley-Adams, Alicestyne (Book collections on Project MUSE., 2022)
"Wilbur H. Siebert published his landmark study of the Underground Railroad in 1898, revealing a secret system of assisted slave escapes. A product of his time, Siebert based his research on the accounts of northern white male abolitionists. While useful in understanding the northern boundaries of the slaves' journey, Siebert's account leaves out the complicated narrative of assistance below the Mason-Dixon Line. In The Gospel of Freedom: Black Evangelicals and the Underground Railroad, author Alicestyne Turley positions Kentucky as a crucial "pass through" territory for escaping slaves and addresses the important contributions of white and black antislavery southerners who united to form organized networks to assist slaves in the Deep South. Drawing on family history and lore as well as a large range of primary sources, Turley shows how free and enslaved African Americans directly influenced efforts to physically and spiritually resist slavery and how slaves successfully developed their own systems to help others who were enslaved below the Mason-Dixon Line. Illuminating the roles of these black freedom fighters, Turley questions the validity of long-held conclusions based on Siebert's original work and suggests new areas of inquiry for further exploration. The Gospel of Freedom seeks to fill the historical gaps and promote the lost voices of the Underground Railroad"--